AN ANNOTATED TRANSLATION OF ANY MINUTE - Agus Wibowo (Journal of English Education, Literature and Linguistics, 2019)
This research is an annotated translation. The object of the research is an English novel entitled Any Minute. The problems of the research are: 1) What are the difficulties the translator/researcher encountered during the process of translating the novel Any Minute? and 2) What are the solutions for those problems/difficulties? The objectives of this research are: a) to attain factual information concerning the problems/difficulties faced by the researcher and b) to solve the problems/difficulties in the course of translating the source text. In this annotated translation research, the translator/researcher uses the introspective and retrospective methods. The result and analysis reveal that there are 2 words, 8 phrases, 2 clauses, 8 sentences, and 5 idioms from the 25 data of the aspects of languages analyzed that were difficult for the translator/researcher. Those difficulties were at the same time became the problems of the translator/researcher. The solutions of the problems were attained by the annotation or analysis done relevant to the translation strategies and translation theories.